2021
DOI: 10.1111/jfb.14899
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of passage efficiency for native and exotic fish species over an artificial baffled ramp

Abstract: This study used an experimental approach to compare the passage success of native and exotic fish species from the temperate Southern Hemisphere over an artificial baffled fish ramp designed for overcoming low‐head (≤1.0 m) fish migration barriers. Passage efficiency was, on average, lower for the exotic species [koi carp (Cyprinus carpio), rudd (Scardinius erythrophthalmus) and rainbow trout (Oncorhynchus mykiss)] compared to the native species [inanga (Galaxias maculatus), redfin bully (Gobiomorphus huttoni)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…In comparison, Franklin and Bartels (2012) recorded a mean of 27% passage efficiency for G. maculatus over a 9-h trial period at a 15-m-long rock ramp, whereas Doehring et al (2011) measured passage efficiencies for G. maculatus of 21-66% over 3-m artificial ramps (artificial grass substrate) at a range of gradients (4-h trial period). Likewise, Baker (2014), Baker and Boubée (2006) and Franklin et al (2021) all recorded 3-h passage efficiencies for G. maculatus ranging from 20 to >90% over experimental fish ramps up to 3 m long with gradients of 15-30°.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In comparison, Franklin and Bartels (2012) recorded a mean of 27% passage efficiency for G. maculatus over a 9-h trial period at a 15-m-long rock ramp, whereas Doehring et al (2011) measured passage efficiencies for G. maculatus of 21-66% over 3-m artificial ramps (artificial grass substrate) at a range of gradients (4-h trial period). Likewise, Baker (2014), Baker and Boubée (2006) and Franklin et al (2021) all recorded 3-h passage efficiencies for G. maculatus ranging from 20 to >90% over experimental fish ramps up to 3 m long with gradients of 15-30°.…”
Section: Discussionmentioning
confidence: 85%
“…salmonids) are competent jumpers and can sometimes make their way past (albeit at lower success rates; Frankiewicz et al 2021), for some small-bodied fishes (<60 mm) it has been demonstrated that vertical drops as little as 0.1 m can effectively prevent upstream passage (Baker 2003). Efforts to overcome these drops, where structure replacement is not an option, have focused on reducing the head drop by raising the downstream water level using rock ramp fishways (Franklin and Bartels 2012;Muraoka et al 2017) or creating artificial ramps that connect to the culvert outlet (Baker 2014;Jellyman et al 2017;Watz et al 2019;Franklin et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The very good passage success of exotic species in the fishway of the Meuse constitutes a collateral adverse effect of the reopening of the migration route that will increase expansion areas, with potential negative impacts for indigenous species (Leuven et al, 2009;McLaughlin et al, 2013). In an experimental approach in a baffle fish-ramp, Franklin et al (2021) observed that passage efficiency was, on average, lower for the exotic species, suggesting that the use of such a selective structure may, in some instances, slow down the progression of invasive species.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, enhanced connectivity with multispecies fishway can be a disadvantage in some situations, allowing the invasion, dispersal and increased recruitment of unwanted and/or exotic species; facilitating the spread of diseases; and providing access to degraded habitats that act as ecological sinks (Franklin et al, 2021). There is an increased interest in focussing some research on both endemic and exotic/non indigenous species.…”
Section: Introductionmentioning
confidence: 99%